Sistem Pakar untuk Mendiagnosis Penyakit pada Ibu Hamil Menggunakan Metode Forward Chaining Berbasis Web (Studi Kasus: RSU Mitra Paramedika Tahun 2024) - Asdistia, Sindy; Wijaya, Dhina Puspasari; Danianti, Dita; Yazid, Ahmad Subhan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The Maternal Mortality Rate (MMR) in Indonesia remains relatively high, partly due to delays in recognizing pregnancy danger signs and the lack of proper monitoring of maternal conditions. Therefore, a technology-based system is needed to support the early detection of pregnancy-related diseases. This study aims to develop a web-based expert system for diagnosing diseases in pregnant women using the forward chaining method with a classical probability approach. The research employed the waterfall model. The system’s knowledge base consists of 15 types of pregnancy-related diseases and 73 symptoms, with diagnostic rules validated by experts. The system was tested using blackbox testing as well as validation of diagnostic results with experts. The results showed that the system was able to produce diagnoses consistent with experts in 14 out of 15 test cases, achieving an accuracy rate of 93.33%. The system is also equipped with a feature for uploading and storing ultrasound (USG) results to support coordination among healthcare facilities. In conclusion, this web-based expert system can be used as an early diagnostic tool and an educational medium for pregnant women, and has the potential to make a significant contribution to reducing maternal mortality in Indonesia.
Keywords: Expert System; Forward Chaining; Pregnancy; Maternal Health; Pregnancy Complications